IDENTIFICATION OF THE FEATURES OF THE INFLUENCE OF HETEROGENEOUS-VELOCITY GROUND LAYERS ON LARGE-EARTHQUAKE EFFECTS IN THE MONGOLIAN-SIBERIAN REGION - V. I. Dzhurik; E. V. Bryzhak; S. P. Serebrennikov; A. A. Kakourova (Геодинамика и тектонофизика, 2024)
The southern part of Eastern Siberia and the northern part of Mongolia were quantitatively assessed in terms of the influence of the upper-crustal heterogeneous-velocity ground layers on a single reasonable initial signal. Seismically, the territory is estimated at 7–9 intensity units; geomorphologically, it appears as a system of intermountain depressions and mountain structures; geologically, the area is a part of the Baikal rift zone system as its southwestern and southern fragments are incorporated therein.The work is aimed at developing methods for studying and predicting seismic effects of large earthquakes in the Mongolian-Baikal region. The implementation of the task is associated with the need of assigning calculated accelerograms, modeling seismic ground motion, and carrying out theoretical calculations for the region under study. Using the data from 2020-2022 relatively large earthquakes recorded simultaneously in Irkutsk and Ulaanbaatar, I category grounds were assigned a single initial signal with regard to potential source zones of near and distant large earthquakes in the region. Computational models of seismic ground motions were developed based on recently obtained seismic survey and seismometric measurement data. The authors also took into account the available general dataset on the change in seismic wave velocities with depth for the most common types of loose unsaturated grounds to a few hundred meters and for the bedrock to the probable depth of earthquake occurrence. The constructed models are characterized by layer thickness, change in longitudinal and transverse wave velocities with depth, volumetric mass, and attenuation decrement.The results of theoretical calculations for the features of the influence of heterogenous-velocity ground layers on the amplitude and frequency composition of the assigned initial signals are presented as the parameters of seismic effects (maximum accelerations, predominant ground motions frequencies and their corresponding amplitude level, resonant frequencies and accompanying ground motions amplification values) for seismic probability models developed based on the calculated accelerograms, spectra, and frequency characteristics.